Cultivation of Uncultured Bacteria of the Class Ktedonobacteria in the Phylum Chloroflexi - Yokota, Akira (UI Scholars Hub, 2012)
The class Ktedonobacteria in the phylum Chloroflexi is known to contain a large number of uncultured, environmental 16S rRNA gene clones, and cultured representatives are a limited number. In this review, recent findings on the taxonomical and ecological significance of the class Ktedonobacteria in the phylum Chloroflexi are discussed based on the findings from both the characteristics of the cultured Ktedonobacteria and molecular-based analysis. The microorganisms characterized so far include four species in three genera, Ktedonobacter, Thermosporothrix and Thermogemmatispora, and were proposed to represent three families, Ktedonobacteraceae, Thermosporotricaceae, and Thermogemmatisporaceae, and two orders, Ktedonobacterales and Thermogemmatisporales. Ktedonobacteria strains showed a common property of gram-positive, aerobic organisms that produce branched vegetative mycelia and form spores by budding.